The Preliminary Results of the DC-Toroidal Discharge Plasma with Axial Electric Field in the Batorm (Global Journal of Science Frontier Research, 2021)
A toroidal plasma system (Batorm) were designed, constructed and developed in Egyptian Atomic Energy Authority (EAEA) since 1998. The plasma parameters of this device have been studied and obtained for the first dimensions during PhD thesis 2003. The word "BATORM" is an abbreviation to "Baby Toroidal of Masoud". The main feature of the system is a low-cost machine which can be operated as a small toroidal plasma device. In this system, the plasma is initiated by linear axial discharge between two plates which create an applied axial field all over the discharge device. This system could be provided rich information on toroidal discharge physics which includes small impurities. The design of the Batorm is upgraded by change its dimensions, according that, the turns number of toroidal, ohmic and vertical coils are increased. The discharge current I dis and total inductance of these three coils were (2 A) and (934.4 μH) respectively. The experimental results have been preliminary taken depending on measurment of electron temperature (KT e ) and ion density (n i ) at each one cm from the outer wall to the inner wall of the chamber. From these results, it is found that the highest values of (KT e ) and (n i ) arrived to 10 eV and 1.52 x10 -9 cm -3 (respectivelely) at distance 7 cm. Besides, it has been seen that there are no plasma arrived to the inner wall according to the toroidal confienment.
Keywords: toroidal plasma/aspect ratio/coils inductance/ electric circuit/ electron temperature and ion density